Development of resource distribution mechanisms between ships at operational work planning of stevedoring company - Махуренко, Геннадий Сергеевич; Круг, Юрий Юрьевич (Technology audit and production reserves, 2015)
The primary goal of industrial - operational planning in the port is establishing the volume and character of reloading works for the planned period, distribution of technical and human resources and developing the actions for performance of this amount of works. In the article it is considered mechanism of industrial - operational planning of works of the stevedoring company. In accordance with the considered resource distribution mechanisms in the ship handling in the port are opening up new possibilities in monthly handling plan of ships; ship handling in shift day time; compiling an optimal handling plan for each ship. The functioning of the resource distribution mechanism consists of three stages. I. The main manager of cargo area informs the chief stevedore about resource distribution mechanism (the number of distributed resources, processing requests of chief stevedore and priorities of ships). II. The main stevedore is reporting requests on resources for ship handling. III. In accordance with the established procedure the main manager of cargo area distributes resources between ships. This mechanism is used in all kinds of operational planning in the port that allows to create a single system of continuous planning of ship handling.